Photo-induced visual response of western flower thrips attracted and repulsed by their phobotaxis spectrum light - Liu, Qihang; Wu, Yuqing; Zhao, Mingfu (International Journal of Agricultural and Biological Engineering, 2022)
This study aimed to clarify the synergistic phototactic attraction-repulsion effect formed by the photo-induced approach-avoidance behavior of thrips, construct phototactic attraction-repulsion light control technologies. The phototactic push-pull effects of red light and UV (365 nm), violet (405 nm), green (520 nm), and yellow (560 nm) single light, as well as their pairwise combined light on the behavior of western flower thrips were investigated using an apparatus that measured thrips response. The study also analyzed the influence of light properties on the phototactic attraction-repulsion effects of thrips and the synergistic effects of red light, and the attraction-repulsion regulation mode. The influence factors on the photo-induced attraction-repulsion effect of thrips were also discussed. The results showed that the red light, presenting the push effect, drove thrips to respond to the sensitive light. The synergistic attraction-repulsion effect of red light and single light, as well as that of red light and combined light was related to the light intensity. However, the attraction-repulsion synergism did not reflect thrips response effect and approach effect pulled and pushed by red light and single light, red light and combined light. Thrips preference for green-yellow light, and their behavior depended on the degree of UV light, making the attraction-repulsion synergy of red and green light the strongest. When the light intensity increased, the attraction-repulsion synergy of red and yellow light was the strongest. The attraction-repulsion response to red light and single light was related to the spectral attribute of the single light, with that of red light and UV light being better. The attraction-repulsion response to red light and combined light was related to light intensity. The intensity of combined light made the attraction-repulsion response to red light and the combined UV and violet light be the best, and the brightness of long-short spectrum light rendered red light and the combined UV and yellow light the best. All such light and combinations were remarkably better than that of red light and UV light. Relative to red light and UV light, the use of red light and combined light provided limited enhancement to the approach effect of thrips; however, under red light and combined light, violet light intensified the approach of thrips to UV light, with yellow light strengthening the approach to green light. Those results provided a scientific basis for the development of light trapping equipment and the adjustment of light control strategies for thrips.Keywords: Western flower thrips, photo-induced visual response effect, attraction-repulsion effect, phobotaxis spectrum light, light intensityDOI: 10.25165/j.ijabe.20221502.7049Citation: Liu Q H, Wu Y Q, Zhao M F. Photo-induced visual response of western flower thrips attracted and repulsed by their phobotaxis spectrum light. Int J Agric & Biol Eng, 2022; 15(2): 48–57.